Kolegialna głowa państwa we współczesnych systemach politycznych - Łukaszewski, Marcin (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2011)
Avast majority of democratic constitutions provide for a unipersonal head of state in modern political systems. There are only four democratic states with a collegial head of state in their political system. In the opinion of the article’s author, this form of the principal state organ is determined by historical factors and/or the federal character of the state. The author also points to the fact that this form of state leadership is present in the political systems of autocratic states.